Assessment of Brand Awareness & Image of Kiehl´s in Portugal & Challenges for their marketing strategy - Schmidt, Sandra (2018)
The principal objective of this dissertation is to investigate the brand awareness of the cosmetic brand Kiehl´s, that is part of the L´Oréal Group, in Portugal. A main goal is to identify the brand perception. Particularly, brand attributes, associations, perceived quality, service and brand loyalty are investigated. To tackle these questionings, a survey was conducted, and additional findings were complemented by the means of a focus group. In course of the literature review, key trends of cosmetics were analyzed ranging from CSR and social engagement, cosmeceuticals through customization and the rising favor for luxury cosmetics. Both in the primary and the secondary research key characteristics of the cosmetics consumer behavior are examined. Additionally, a comparison of Kiehl´s principal competitors is undertaken and general key success factors for the cosmetic industry are carried out. Main conclusions of this paper are that there is potential for improvement in connection with the brand awareness, yet the brand perception of Kiehl´s is greatly favorable perceived by the Portuguese population. In consideration of these findings, the main recommendations target the improvement of brand awareness taking the crucial success factors into account. Last but not least, Kiehl´s enjoys an excellent basis regarding external trends and superb prerequisites to succeed in the cosmetic industry in present and in future.